2011
DOI: 10.2355/isijinternational.51.1086
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Model of Oxygen Steelmaking Part 1: Model Development and Validation

Abstract: A comprehensive model of oxygen steelmaking that includes the kinetics of scrap melting, flux dissolution, slag chemistry, temperature profile of the system, formation and residence of metal droplets in the emulsion, and kinetics of decarburization reaction in different reaction zones was developed. This paper discussed the development and the application of the model into an industrial practice. The results from the model were consistent with the plant data from the study of Cicutti et al. The model suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 23 publications
2
86
0
2
Order By: Relevance
“…This work formed the basis of the Bloated Droplet Model, which has since been employed in an overall BOF model by workers at Swinburne University in Australia. [20,21] Notwithstanding very recent work, which suggests bubbles formed on the outer surface of droplets can offer similar increases in residence time, convincing experimental evidence for bloated droplets has been reported by several researchers. [5,6,29] Given the importance of droplet swelling in controlling residence time and the fact that dephosphorization is only favored when slag and metal are in contact, data on dephosphorization of bloated droplets are required for the proper inclusion of dephosphorization in BOF process models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work formed the basis of the Bloated Droplet Model, which has since been employed in an overall BOF model by workers at Swinburne University in Australia. [20,21] Notwithstanding very recent work, which suggests bubbles formed on the outer surface of droplets can offer similar increases in residence time, convincing experimental evidence for bloated droplets has been reported by several researchers. [5,6,29] Given the importance of droplet swelling in controlling residence time and the fact that dephosphorization is only favored when slag and metal are in contact, data on dephosphorization of bloated droplets are required for the proper inclusion of dephosphorization in BOF process models.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied aspects of droplet behavior relevant to steelmaking including, decarburization, [1][2][3][4][5][6] droplet generation, [7][8][9][10][11][12][13][14][15][16] size distribution, [17,18] and residence time. [19] Other workers have developed models [20][21][22][23] and conducted plant trials, [24][25][26][27][28] which considered the role of droplets in the overall process kinetics. Previous work in the authors' laboratory [6] showed that droplet swelling, caused by CO formation inside the droplet, increased the droplet residence time in the slag, thereby favoring decarburization.…”
Section: Introductionmentioning
confidence: 99%
“…Reported residence times ranging from 0.4 to 120 seconds are given, with an average of around 40 seconds. [24][25][26][27][28][29][30] The amount of metal in the emulsion has been reported in a complete range of up to 50 pct of the tap weight dependant on blow time. [31,32] With regard to the kinetics of a specific metal droplet in the emulsion, several authors have investigated variable aspects (point 3 & 4 above).…”
Section: Introductionmentioning
confidence: 99%
“…Kattenbelt and Roffel [52] developed a model to describe the response of oxygen steelmaking to step changes in process variables such as oxygen blow rate, lance height and oxide additions. These workers used insights obtained from work on droplet generation, size distribution and residence time to define the parameters to be considered in an empirical relation for decarburization rate.…”
Section: Practical Application Of Kineticsmentioning
confidence: 99%